Relevansi Pemikiran Filsafat Islam dalam Kajian Ilmu Pendidikan Islam - Ramli, Ramli; Marjuni, A.; Achruh, Andi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the relevance of Islamic philosophical thought in the study of Islamic education. This study uses a literature review methodology to explore the relevance of Islamic philosophical thought in the study of Islamic education. This method involves collecting, analyzing, and synthesizing data from a variety of scientific sources, including books, journal articles, and other academic publications related to Islamic philosophy and educational sciences. The selected literature is critically analyzed to uncover the relationships, patterns, and potential contributions of Islamic philosophy to educational theory and practice. In addition, this study uses a thematic analysis approach to categorize the findings and draw conclusions regarding the alignment between Islamic philosophical principles and the goals of Islamic education. The findings of this study are the urgency and function of Islamic education philosophy for educators and Islamic education thinkers. Education without being imbued with philosophy, the education will not be able to run well and perfectly, as well as will have difficulties in determining the expected direction and goals. The purpose of Islamic educational philosophy is essentially identical to the purpose of Islamic teachings. Both come from the same source, namely the Qur'an and al-Hadith. The philosophy of Islamic education has a role in two directions, namely the development of philosophical concepts of Islamic education will automatically produce new theories in Islamic education and the improvement and renewal of the implementation of Islamic education